''Mr. C. MacPherson, manager Royal Stores.'' - Job, John (William John), b. 1944- (1905)
Campbell MacPherson, manager Royal Stores Ltd. sitting at his desk in his office. This collection consists of photographs taken from two Job family albums, reflecting their business ventures, family activities and historical events.